Brainy bunch montessari / Asyraf Nazrul Haqim Zamzubir - Zamzubir, Asyraf Nazrul Haqim (2022)
was founded in 2010, the founder is Encik Mohd Fadzil Hashim he had a dream to provide muslim children a modern education whilst also catering for their islamic identity and up bringing. through sheer dedication and hard work which began as a modest family operated kindergarten has gone on to become the first montessori elementary school and probably the best know islamic montessori preschool francise in asia.